(untitled) - Yoshida, Shigeru (Boston, 1962)
The history of those climatic years has been recorded in detail and by many pens on the Allied side. These memoirs portray something of the course events as seen through eyes of one who was close to development on the Japanese side and who eventually was cast for a prominent role in the greatest ever to confront.
Keywords: Nhật Bản,Japan; Lịch sử,History; Đồng minh chiếm đóng, 1945-1952,Allied occupation, 1945-1952